Production of knowledge based on the Theory of Culture Care Diversity and Universality: documental research - Maria Helena Lenardt; Tatiane Michel; Susanne Elero Betiolli; Marcia Daniele Seima; Fátima Denise Padilha Baran; Conceição da Silva Brito (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objectives: To analyze the abstracts that relate nursing to the Theory of Culture Care Diversity and Universality, published in the annals of the main national scientific events in the category, over a 12-year period. Methods: documental research carried out in the annals of the Brazilian Nursing Congress and the National Nursing Research Seminar. Data collection took place from July/2018 to June/2019 using a form. Data was analyzed using descriptive statistics and content analysis. Results: 99 studies were analyzed, and three categories emerged: Cultural diversity, emic perspective, and cultural context: possibilities for applying the theory; Incongruencies and peculiarities of the care sectors: limitations of the application of the theory; Knowledge production to improve care: implications for professional nursing practice. Final Considerations: the investigated scientific production enabled the construction of knowledge of cultural aspects related to nursing care and showed similarities and variations in care practices.